Magnetite/graphene oxide nano-composite for enhancement of hydrogen production from gelatinaceous wastewater. (September 2016) - Mostafa, Alsayed; El-Dissouky, Ali; Fawzy, Amal; Farghaly, Ahmed; Peu, Pascal; Dabert, Patrick; Le Roux, Sophie; Tawfik, Ahmed
Graphical abstract: Highlights: The fermentation of protein rich wastewater is commonly incomplete. Protein degradation increased by supplementation of anaerobes with MGO. Supplementation of sludge with magnetite graphene oxide improved H2 production. Addition of magnetite/graphene oxide nanocomposite increased the hydrogenase activity. MGO reduced microbial diversity and enriched H2 producers densities. Abstract: The effect of substrate to inoculum (So /Xo ) ratio and supplementation of magnetite/graphene oxide (MGO) nano-composite material on hydrogen production from gelatinaceous wastewater via dark fermentation process was investigated. Results demonstrated that optimum So /Xo ratio of 1.0 gCOD /gVSS achieved maximal hydrogen yield (HY) of 79.2 ± 11.9 mL H2 /gCOD removed . Supplementation of anaerobes with 100 mg/L MGO promoted HY up to 112.4 ± 10.5 mL H2 /gCOD removed . Moreover, the degradation efficiency of carbohydrates, proteins and lipids was improved to 80.8 ± 7.6, 34.4 ± 2.3 and 31.4 ± 2.2%, respectively. Acetate (HAc) and butyrate (HBu) concentrations increased from 102 ± 6.8 to 125.3 ± 6.3 and from 31.1 ± 1.5 to 48.8 ± 3.5 mg/gVSS, respectively. However, propionate (HPr) concentration dropped from 35.9 ± 2.7 to 15 ± 1.3 mg/gVSS . Hydrogenase enzyme activity increased 9-folds and the anaerobes elongated from ca. 1.8–2.9 to ca. 2.5–5.1 μm with MGO addition. Moreover, Proteobacteria, Firmicutes, Clostridia and Bacilli were detected with the batches supplemented with MGO.